Chinese Herbal Medicine for Aspirin Resistance: A Systematic Review and Meta-Analysis. - Hanyu Chen; Zhengjie Shen; Jiandong Chen; Haowen Zhang; Xiaohu Chen (PLoS ONE)
Objectives To assess the effectiveness and safety of Chinese herbal medicine (CHM) for the treatment of aspirin resistance (AR). Methods A comprehensive research of seven electronic databases was performed for comparative studies evaluating CHM for AR. Two authors independently extracted data and assessed the methodological quality of the included trials using the Cochrane risk of bias tool. Data wasere synthesized by using RevMan 5.3 software. (PROSPERO Registration #CRD42015020182). Results 18 randomized controlled trials (RCTs) involving 1,460 patients were included. 15 RCTs reported significant difference in the reduction of platelet aggregation rate (PAR) induced by adenosine diphosphate (ADP) (P<0.05), and 11 reported significant effect of CHM plus aspirin to reduce PAR induced by arachidonic acid (AA) (P<0.05) compared with aspirin 100mg/d treatment. The pooling data of 3 RCTs showed the thromboxane B2 (TXB2) in patients with CHM plus aspirin versus aspirin were significantly reduced (Random Effect model (RE), Standard Deviation (SD) = -95.93, 95% Confidential Interval (CI)[-118.25,-73.61], P<0.00001). Subgroup analysis showed that TXB2 (Fixed Effect model (FE), SD = -89.23, 95%CI[-121.96,-56.49], P<0.00001) had significant difference in Tongxinluo capsule plus aspirin versus aspirin. 2 RCTs reported the clinical effective rate, and the meta-analysis result showed a significant difference in intervention and control group (FE, Relative Risk (RR) = 1.67, 95%CI[1.15, 2.42], P = 0.007<0.05). In 4 trials, CHM plus aspirin had better effects of reducing the reoccurrence of cerebral infarction than aspirin (FE, RR = 0.24, 95%CI [0.11, 0.49], P<0.0001). And one trial showed that CHM plus aspirin could decrease the National Institutes of Health Stroke Scale (NHISS) score (P<0.05) and increase the Barthel Index (BI) score (P<0.05). 4 trials stated that there were no adverse effects occurred in intervention group, and analysis showed significant difference of CHM or CHM plus aspirin in reducing the occurrence of adverse events (FE, RR = 0.22, 95%CI[0.13, 0.39], P<0.00001). 5 trials claimed that the CHM monotherapy and CHM adjunctive therapy for AR did not add the risk of bleeding (FE, RR = 0.50, 95%CI[0.20, 1.22], P = 0.13>0.05). Conclusions CHM may be effective and safe as an alternative and collaborative therapy for AR. However, the current evidence and potential promising findings should be interpreted with caution due to poor and varying methodological quality of included studies and the heterogeneity of interventions. Thus, further exploration of this strategy with adequately powered RCTs is warranted.